Causality Analysis between ESG Performance and Financing Support: Case Study Mining Holding Company in Indonesia - Mahardhika, Galih S; Raka Achmad, Inggis; Putri, Kusuma Hani (Journal of Business and Political Economy : Biannual Review of The Indonesian Economy, 2021)
Recent global trends in electric vehicles (EV) triggered Indonesia to participate in battery industry development. Rich in geological resources, the government promotes various capital-intensive industries that process raw mining commodities, particularly limonite nickel ore, to support the EV industry in Indonesia. Inarguably, financial support is needed from various financial institutions and investors. On the contrary, the mining industry is closely related to environmental issues that attract the attention of financial institutions and investors. Therefore, understanding the relationship between “sustainability” and “financing activity” is essential, as it may not only practically guide the business to re-examine their environmental, social, and governance (ESG) initiatives but also extend the literature review on these matters. Therefore, this paper aims to describe the system through the Causal Loop Diagram (CLD) formed by ESG factors related to the financing process in mining companies in Indonesia. The research method used in this paper is developing causal loop diagrams from primary data and literature reviews. The CLD is constructed through a literature review and confirmed by an expert from the mining company. The result explains the causal loop between sustainability and financing. Improving ESG performance will increase financial support from global investors and financial institutions. To support practice and concept sustainability in Indonesia, the government should encourage mining companies to increase local partnerships and CSR Allocation as it will support the company's financing activity and trigger community improvement. Creating a supporting environment to attract global investors to finance the mining company in Indonesia is also necessary.  Keywords: Causal Loop Diagram, ESG Performance, Financial Performance, Mining Industry, Sustainability JEL : M14, Q01, G32